A solitary mud-daubing wasp, Brachymenes dyscherus (Hymenoptera: Vespidae) fron Brazil with evidence of a life-cyde polyphenism - Camillo, Evandro (Universidad de Costa Rica, 1999)
Nests ( n=60 ) of a solitary mud-daubing wasp, Brachymenes dyscherus were conected at Fazenda Santa Carlota, Cajuru, Sao Paulo, Brazil ín 1995 and 1996 . The multi-celled mud nests were constructed on the interior walls of abandoned houses in dry and shaded places. Nests were composed of 1 to 4 layers with cens constructed in two paralle! series. The number of cens per nest ranged from 3 to 62. Cells containing prey (larvae of Lepidoptera) numbered fram 4 to 29. B. dyscherus is a uniyoltíne species. Adults emerge from September to December, and nesting talces place at the beginning of the following year; however, the developmental period for some immatures with proloFlged diapause l3.Sted up to 596 days. The total duration of immature stages n nests collected in 1996 was less for males than for females. The sex ratio for the total populatíon was 1 . 5 males: 1 female with males emerging earher than females. A life table was constructed, and details of lhe life cycle of the wasps and parasitoids are presented. The mos! common mOl1ality factors were either endogenous or due 10 Melittobia sp. (Eulophidae) .